Pengaruh Intervensi Kognitif Spiritual Terhadap Penerimaan Diri Pada Klien Stroke Iskemik - Novita Setyowati; Uswatun Hasanah (Akademi Keperawatan Dharma Husada Kediri, 2016)
Hemiparese is a common problem that can caused disability. Exercise is still considered effective to prevent disability. This study is aimed to increased the muscle strength on hemiparese patient's muscle strength caused by ischemic stroke in RSUD Gambiran Kota Kediri. This study used Quasi Experiment pre and post test research designs. Number of samples were 9 respondents who were divided into intervention group and control group. Evaluation research was done on the first day and eigth day for the two groups. Data were analyzed Paired T test and Independent T Test. Study results showed an increased in muscle strength (p =0.000) in both the intervention groups and there are significant differences between the two groups (p = 0009), which means there is a difference between the control group treatment group. The implication of this research are to use exercise as one of the independent nursing interventions in caring stroke patients with hemiparase and to improve the quality of nursing care, makes healing process faster, prevent complications dan also enrich nursing science. Keywords: stroke; hemiparese; Spiritual intervention on cognitive; Self acceptance.